(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
Two simple and sensitive Vis spectrophotometric methods were developed for the determinationof paracetamol and compared with the specific and rapid UV spectrophotometric method at243nm for the simultaneous quantification in standard solutions and tablets. The first methodinvolves determination of paracetamol by using a vanaline as a reagent in the presence of 1MHCl to produce a stable yellow- orange color Schiff base absorbs at 392 nm after fraction of itby 4M H2SO4.The second method involves using alkaline potassium permanganate as anoxidizing agent produucing a stable blue-green color absorbs at 606 nm after fraction of it by 4MNa0H ,The paracetamol pKa value (9.537) was calculated from absorbance measurement atparticular wave length in acidic, basic and buffer solution (pH=9) the result approch to the truevalue.